THE DEVELOPMENT AND STUDY OF THE TOXICITY OF SUPPOSITORIES WITH A MODIFIED SUBSTANCE OF INTERFERON ALFA-2B - ANUROVA, MARIA N.; BAKHRUSHINA, ELENA O.; SHUMKOVA, MARINA M.; DEMINA, NATALIA B.; KRASNYUK, IVAN I. (International Journal of Applied Pharmaceutics, 2023)
Objective: To develop a stable composition with the substance of PEGylated interferon alfa-2b, to study technological and biopharmaceutical characteristics of the dosage form, and to conduct preclinical studies on the chronic toxicity and local irritating effect. Methods: Solid fats Witepsol® H15, Witepsol® W 35, Suppocire® BS2X, and Suppocire® BM brands were used as the suppository bases. Polysorbate 80 was used as an emulsifier. Citric acid, ascorbic acid, sodium tetraborate, lactic acid, ethylenediaminetetetraacetic acid, tocopherol acetate was also introduced into the experimental samples. Fourteen experimental samples were screened for biological and technological indicators. Preclinical studies were performed for the optimal composition on the indicators of chronic toxicity and local irritant effect. Results: The study examined the cytotoxic effects on the Vero cell line of selected suppository bases and excipients, namely, pH regulators and antioxidants. With excipients that did not have cytotoxicity we obtained suppository compositions with the following quality indicators: cytotoxicity, specific activity of interferon, time of complete deformation of suppositories and their melting temperature. A total of 14 compositions were studied, of which 5 were selected on the basis of the results for the study of stability. Only one composition turned out to be stable for the time studied. Conclusion: The most stable in terms of “specific activity” was sample 7, its composition: Witepsol® H15/W35 70/30, polysorbate-80 0.15%, ethylenediaminetetraacetic acid (EDTA) 0.15%, sodium tetraborate 0.15%, tocopherol acetate 3.0%. Preclinical studies, that showed the absence of chronic toxicity and local irritant effect, were performed for this composition.